Kinetic Evaluation of Ammonium Based Ionic Liquids for CO2 and CH4 Hydrates Mitigation - Ali Osman, Ola Abdalgawi (Universiti Teknologi PETRONAS, 2016)
Prevention of gas hydrate formation is critical to the oil and gas Industry because it disturbs gas flow, plug pipeline and result in economical and safety issues. Kinetic Inhibition is the cost effective way; Conventional kinetic inhibitors have many limitations. Recently Ionic liquids (ILs) are proposed for gas hydrates field as kinetic inhibitors and better kinetic performance was recorded for ILs with Amide group which called as Ammonium based Ionic Liquids (AILs). The desired Kinetic inhibition has not been reported yet and door for further investigation is open due to variety available AIls. The present work studied the kinetic of tetra methyl ammonium hydroxide (TMAOH) and tetra methyl ammonium chloride (TMACl) on carbon dioxide and methane hydrates at high degrees of sub-cooling. Tests were conducted in high-pressurised vessel with agitation. Using Pressure of 35 for CO2 and 80 bar for CH4, 0.5 ,1 and 2 wt% were the AILs concentration tested at 4 C and 1C sub-cooling temperatures. Three kinetic parameters were measured in this study: Induction time, hydrate formation rate and gas consumption. Results suggest that TMAOH and TMACl has potential to be used for flow assurance strategies.